2020
DOI: 10.3390/molecules25061283
|View full text |Cite
|
Sign up to set email alerts
|

Quinolinecarboxamides Inhibit the Replication of the Bovine Viral Diarrhea Virus by Targeting a Hot Spot for the Inhibition of Pestivirus Replication in the RNA-Dependent RNA Polymerase

Abstract: The bovine viral diarrhea virus (BVDV), a pestivirus from the family of Flaviviridae is ubiquitous and causes a range of clinical manifestations in livestock, mainly cattle. Two quinolinecarboxamide analogues were identified in a CPE-based screening effort, as selective inhibitors of the in vitro bovine viral diarrhea virus (BVDV) replication, i.e., TO505-6180/CSFCI (average EC50 = 0.07 µM, SD = 0.02 µM, CC50 > 100 µM) and TO502-2403/CSFCII (average EC50 = 0.2 µM, SD = 0.06 µM, CC50 > 100 µM). The initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…It was observed that although the derivatives inhibited the wild-type replication complexes, they could not inhibit mutant replication complexes. Interestingly, the derivative ( 2) did inhibit the activity of replication complexes but they could not inhibit the purified RdRp [46] .
Figure 4 SAR profile of compound 2 as anti-BVDV agent.
…”
Section: Rdrp Inhibitors For Various Viral Infectionsmentioning
confidence: 99%
“…It was observed that although the derivatives inhibited the wild-type replication complexes, they could not inhibit mutant replication complexes. Interestingly, the derivative ( 2) did inhibit the activity of replication complexes but they could not inhibit the purified RdRp [46] .
Figure 4 SAR profile of compound 2 as anti-BVDV agent.
…”
Section: Rdrp Inhibitors For Various Viral Infectionsmentioning
confidence: 99%
“…These results suggest that NS5B is a promising target for antiviral research. As reported, Quinoline carboxamide analogs can be used as selective inhibitors of BVDV replication in vitro by inhibiting the activity of BVDV RdRp [ 2 , 80 ], whereas guanosine triphosphate (GTP) can stimulate the RdRp activity of NS5B. However, the synergistic effect of NS3 and NS5B in the host is required to synthesize viral RNA (Table 1 ).…”
Section: Non-structural Proteinsmentioning
confidence: 99%
“…Molecular modeling studies performed with most previously reported BVDV NNI inhibitors, such as TSC (Castro et al, 2011), BPIP (Paeshuyse et al, 2007), VP32947 (Baginski et al, 2000), LZ37 (Paeshuyse et al, 2009), benzimidazole (Asthana et al, 2013), and CSFCII (Musiu et al, 2020), have shown that these compounds bind to a hydrophobic cavity limited by amino acids F224, I390, A392, and L225. This allosteric site was defined as a "hot spot" for the inhibition of virus replication.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…The use of antiviral agents could be an attractive strategy as a stopgap measure to prevent infection in naïve calves (Newcomer et al, 2014). Moreover, antivirals could also be used to treat valuable animals infected with pestiviruses in zoological collections and in in-breeding programs and in vitro embryo production, to cure established cell lines contaminated with pestiviruses, which are used, for example, to produce interferons and vaccines for medical use (Stringfellow et al, 2005;Newcomer and Givens, 2013;Newcomer et al, 2014;Musiu et al, 2020). However, no antivirals are currently available for controlling BVDV infections in either laboratories or farms.…”
Section: Introductionmentioning
confidence: 99%